Potential impact of pocket gopher (Orthogeomys sp.) on peach palm (Bactris gasipaes) crop in Costa Rica. - Monge, Javier (Agronomía Mesoamericana, 2006)
The taltuzas (pocket gopher) (Orthogeomys sp.) are rodents that plague several crops from USA to Panama. Peach palm (Bactris gasipaes) is a crop in expansion that overlaps in its geographical distribution with the one of Pocket gopher. Three patterns were found by superposing the distribution maps of rodents and palms. In one pattern only one organism was present but not the other whereas in two patterns rodents and palms were coincident. Since peach palm is attacked by the taltuzas, some considerations were discussed for each pattern in relation to future expansion of this crop.